Steps Toward Modelling the Past and Future North Sea Ecosystem With a Focus on Light Climate - Thewes, Daniel; Stanev, Emil V.; Zielinski, Oliver (Frontiers in Marine Science, 2022)
With ongoing man-made climate change, it is important to understand its impact on regional ecosystems. Furthermore, it is known that the North Sea light climate is subject to ongoing change. The combined effects of climate change and coastal darkening are investigated in this work. We used a three-dimensional ecosystem model, forced with data from a climate model, to project three plausible biogeochemical states for the years 2050-2054, following three representative concentration and shared socioeconomic pathways (RCP2.6-SSP1, RCP4.5-SSP2 and RCP8.5-SSP5). We also performed a historic experiment for the years 1950-1954 and 2000-2004 for comparison. Our results suggest significant reductions of phytoplankton biomass as a consequence of sinking nutrient levels for all future scenarios. Additionally, a modelling study was carried out, in which we raised background SPM levels by 40% to reflect potential changes in the future. This revealed that for RCP2.6-SSP1, the ecosystem is more sensitive to changes in the light climate than for the other scenarios, due to higher nutrient availability.